The Unfolded Protein Responses in Health, Aging, and Neurodegeneration: Recent Advances and Future Considerations - Wodrich, Andrew P. K.; Scott, Andrew W.; Shukla, Arvind Kumar; Harris, Brent T.; Giniger, Edward (Frontiers in Molecular Neuroscience, 2022)
Aging and age-related neurodegeneration are both associated with the accumulation of unfolded and abnormally folded proteins, highlighting the importance of protein homeostasis (termed proteostasis) in maintaining organismal health. To this end, two cellular compartments with essential protein folding functions, the endoplasmic reticulum (ER) and the mitochondria, are equipped with unique protein stress responses, known as the ER unfolded protein response (UPRER) and the mitochondrial UPR (UPRmt), respectively. These organellar UPRs play roles in shaping the cellular responses to proteostatic stress that occurs in aging and age-related neurodegeneration. The loss of adaptive UPRER and UPRmt signaling potency with age contributes to a feed-forward cycle of increasing protein stress and cellular dysfunction. Likewise, UPRER and UPRmt signaling is often altered in age-related neurodegenerative diseases; however, whether these changes counteract or contribute to the disease pathology appears to be context dependent. Intriguingly, altering organellar UPR signaling in animal models can reduce the pathological consequences of aging and neurodegeneration which has prompted clinical investigations of UPR signaling modulators as therapeutics. Here, we review the physiology of both the UPRER and the UPRmt, discuss how UPRER and UPRmt signaling changes in the context of aging and neurodegeneration, and highlight therapeutic strategies targeting the UPRER and UPRmt that may improve human health.